FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN TAHU DI KECAMATAN PAMONA SELATAN KABUPATEN POSO - Lidyawati, Irma; Antara, Made; Laksmayani, Made Krisna (Fakultas Pertanian, Universitas Tadulako, 2023)
Tofu is a popular and nutritionally balanced food, widely favored as a side dish among people. The aim of this study was to investigate the factors affecting the demand for tofu in Pamona Selatan Sub District of Poso District, focusing on the influence of tofu price, tempeh price, consumer income, the number of dependents in the consumer's family, and the age of the consumer. The analysis revealed that, among the five variables examined, namely tofu price, tempeh price, consumer income, number of family dependents, and consumer age, only tofu price, the number of family dependents, and consumer age had a significant effect on the demand for tofu in Pamona Selatan sub-district, Poso Regency. On the other hand, the price of tempeh and consumer income did not show any significant effect on the demand for tofu in this region. The R2 calculation indicated that approximately 69.1% of the variation in tofu demand in South Pamona District, Poso Regency, can be explained by the variables such as tofu price, tempeh price, the number of dependents in the consumer's family, and the age of the consumer. The remaining percentage is attributed to other variables that were not considered in this study.